Breaking away how great leaders create innovation that drives sustainable growth--and why others fail - Stevenson, Jane 1962-; Kaafarani, Bilal (New York McGraw-Hill, 2011)
The key to generating growth and shareholder value today is the ability to develop and embed innovation into every fact of business.
The innovation equation -- The leadership equation -- The payoff: activating growth.
Dr. Mary Gretchen F. Chaves (Recommending faculty) : Management Cluster
Includes bibliographical references (p. 225-229) and index.
Keywords: Creative ability in business; Leadership; New products